Preservice Principals' Post-Internship Concerns About Becoming a Principal: America and Scotland in Review - Mack T. Hines III (Educational Considerations, 2008)
The capstone experience of teacher preparation and principal preparation programs is generally the internship. These experiences should provide preservice teachers and principals with the opportunities to develop their skills in teaching and school leadership respectively.
Keywords: preservice principals; teachers; theoretical; framework; instructional; materials; American; Scottish; concerns; review; analysis; leadership; experiences